A probabilistic estimate of global marine N-fixation and denitrification - Eugster, Olivier; Gruber, Nicolas (Global biogeochemical cycles, 2012)
We determine the global rates of marine N-fixation and denitrification and their associated uncertainties by combining marine geochemical and physical data with a new two-dimensional box model that separates the Atlantic from the IndoPacific basins. The uncertainties are estimated using a probabilistic approach on the basis of a suite of 2500 circulation configurations of this box model. N-fixation and denitrification are diagnosed in an inverse manner for each of these configurations using N*, P*, and the stable nitrogen isotope composition of nitrate as data constraints. Our approach yields a median water column denitrification rate of 52 TgN yr1 (39 to 66 TgN yr1, 5th to 95th percentile) and a median benthic denitrification rate of 93 TgN yr1 (68 to 122 TgN yr1). The resulting benthic-to-water column denitrification ratio of 1.8 confirms that the isotopic signature of water column denitrification has a limited influence on the global mean stable isotopic value of nitrate due to the dilution of the waters with a denitrification signal with the remainder of the ocean's nitrate pool. On the basis of two different approaches, we diagnose a global N-fixation rate of between 94 TgN yr1 and 175 TgN yr1, with a best estimate of 131 TgN yr1 and 134 TgN yr1, respectively. Most of the N-fixation occurs in the IndoPacific suggesting a relative close spatial coupling between sources and sinks in the ocean. Our N-fixation and denitrification estimates plus updated estimates of atmospheric deposition and riverine input yield a pre-industrial marine N cycle that is balanced to within 3 TgN yr1 (38 to 40 TgN yr1). Our budget implies a median residence time for fixed N of 4,200 yr (3,500 to 5,000 yr).